Integrasi Pendidikan Agama Kristen dalam Menangani Krisis Kesehatan Mental pada Generasi Z dalam Konteks Menuju Indonesia Emas 2045 - Marsaulina, Roce; Majesty, Gilbert Timothy (STT Pelita Dunia, 2025)
The integration of Christian religious education in efforts to address the mental health crisis faced by Generation Z in Indonesia is very important, with a focus on its contribution to realizing the Golden Indonesia 2045. Generation Z, born in the digital era, is exposed to significant mental health challenges, such as anxiety, depression, and feelings of isolation, which are further exacerbated by social pressures and digitalization. In this context, Christian religious education can serve as a vital source of moral and spiritual support in building mental resilience. Through Christian teachings that emphasize love, forgiveness, and hope, Generation Z can gain a strong foundation in facing various life challenges. This article adopts a qualitative approach, analyzing literature and the practice of Christian religious education in Indonesia to examine its impact on the mental health of adolescents. It was found that the integration of Christian religious education into the education system can have a positive impact on mental health by introducing values that encourage self-awareness, emotional control, and healthy social skills. In addition, Christian teachings can also facilitate the process of mental healing by fostering a more optimistic worldview based on strong beliefs. This article proposes that by more broadly integrating Christian religious education into the national education curriculum, Indonesia can create a Generation Z that is more resilient mentally, socially, and spiritually, and ready to welcome the Golden Indonesia 2045 as a highly competitive and noble-charactered nation.